2005
DOI: 10.1007/s10067-005-0106-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of IL-18, IL-15, IL-12 and TNF-α measurement in rheumatoid arthritis

Abstract: The aim of the study was to evaluate the clinical significance of serum (S) and synovial fluid (SF) interleukin (IL)-18, IL-15, IL-12 and the tumor necrosis factor alpha (TNF-alpha) measurements in relation to laboratory and clinical measures of disease activity of patients with active rheumatoid arthritis (RA). Sixty-four patients with RA and 25 patients with osteoarthritis (OA) were included in this study. RA activity was determined using the Disease Activity Score (DAS) 28 index. Concentrations of IL-18, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 9 publications
4
76
1
1
Order By: Relevance
“…However, it is now clear that this cytokine also has a function in chronic joint inflammation (Sukedai et al, 2004;Emshoff et al, 2000). High levels of TNF-a are detected by ELISA in the SF of human patients with chronic RA (Isomaki et al, 1996;Lettesjo et al, 1998;Petrovic-Rackov and Pejnovic, 2006). In addition, clinical trials targeting TNF-a (anti-TNF-a antibodies, soluble TNF-a receptors) ameliorate disease symptoms in patients with acute and chronic RA (Brennan et al, 1995;Macias et al, 2005).…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…However, it is now clear that this cytokine also has a function in chronic joint inflammation (Sukedai et al, 2004;Emshoff et al, 2000). High levels of TNF-a are detected by ELISA in the SF of human patients with chronic RA (Isomaki et al, 1996;Lettesjo et al, 1998;Petrovic-Rackov and Pejnovic, 2006). In addition, clinical trials targeting TNF-a (anti-TNF-a antibodies, soluble TNF-a receptors) ameliorate disease symptoms in patients with acute and chronic RA (Brennan et al, 1995;Macias et al, 2005).…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Based on previous studies that reported the stimulatory effect of IL-18 on GM-CSF expression in CD4 + T cells [11][12][13] , we hypothesized that the free IL-18BP in culture supernatants derived from RANKL-treated RAW264. An increase in the level of IL-18 has been observed in the serum or pathological tissue in individuals with rheumatoid arthritis [28][29][30][31] or periodontitis 32,33) , both of which are well-recognized as inflammatory diseases with bone destruction, through RANKLinduced osteoclast formation [34][35][36] . The results in our present study may help explain how RANKL, IL-18 and IL-18BP are involved in the cell-cell interactions between osteoclast precursor cells and CD4 + T cells in these bone-destructive disorders.…”
Section: Effect Of Conditioned Medium Derived From Raw2647 Cells On mentioning
confidence: 99%
“…These findings suggest that IL-15 might represent a new immunomodulatory and anabolic tool for the treatment of cachexia associated with metastatic malignancies (Waldmann et al, 2011). However, the potential application of IL-15 in other conditions associated with inflammatory cachexia syndrome should be carefully evaluated because IL-15 is also proposed as an important factor in pathogenesis of several chronic inflammatory diseases such as rheumatoid arthritis (Petrovic-Rackov & Pejnovic, 2006). Contradictory findings have been obtained in possible involvement of IL-15 in sarcopenia, the degenerative loss of skeletal muscle mass and strength associated with aging, in rats.…”
Section: The Role Of Cytokines In the Muscle Catabolismmentioning
confidence: 99%
“…Moreover, particularly IL-6, whose level is dependent on stimulation of TNFand IL-1, predicts mortality in patients with end-stage renal disease (Cheung et al, 2010). In patients with rheumatoid arthritis, the overproduction of TNF-and IL-1 is associated with hypermetabolism and reduced body cell mass, and serum concentrations of these cytokines as well as IL-6, IL-15, IL-18, and IL-12 correlate strongly with disease severity (Roubenoff et al, 1994;Petrovic-Rackov & Pejnovic, 2006;de Paz et al, 2010). Patients with COPD also exhibit an increase in resting energy expenditure and a decrease in free-fat mass, and these patients have markedly increased acute phase reactant proteins and inflammatory factors (IL-8, soluble TNF receptors: sTNF-R55 and sTNF-R75) in their serum (Schols et al, 1996).…”
Section: Cytokines and Cachexia-related Chronic Diseasesmentioning
confidence: 99%